ANESTHETIC EFFECT OF TRICAINE METHANESULFONATE IN JUVENILE PAICHES (ARAPAIMA GIGAS) - Hinostroza M., Elizabeth (2013)
The objective of the present study was to evaluate the effectiveness of tricaine methanesulfonate (MS-222) as anesthetic in six juvenile paiches (Arapaima gigas)(180-243 days) with a body weight of 730 g. The specimens were brought from the Iquitos city to the Universidad Peruana Cayetano Heredia in Lima. They were exposed in four opportunities to four doses of MS-222 (25, 50, 75, and 100 mg/L) to evaluate the duration of induction and recovery as well as the survival rate post anesthesia. The opercular ventilation frequency was counted and heart rate was measured by ultrasound. Blood samples were collected and the haemogram values were obtained pre and post anesthesia. The induction period was shorter and the recovery period was higher when the concentration of anesthetic was increased. None statistical differences were found in the haemogram or in physiological values before and after anesthesia. It was concluded that the MS-222 (100 ppm) have efficient anesthetic effects in paiches at the 100 mg/L concentration.